Intracoronary epinephrine and verapamil in the refractory no-reflow phenomenon in patients with acute myocardial infarction - S. V. Dil; E. V. Vyshlov; V. V. Ryabov (Кардиоваскулярная терапия и профилактика, 2022)
Despite modern advances in performing percutaneous coronary interventions, refractory no-reflow remains a serious problem that worsens in-hospital and long-term prognosis. Low-dose adrenaline may exhibit potent beta-receptor agonist properties that mediate coronary vasodilation.Aim. To evaluate the efficacy and safety of intracoronary administration of epinephrine and verapamil, as well as their combination, compared with standard treatment in patients with ST-segment elevation myocardial infarction (STEMI) and refractory no-reflow during percutaneous coronary interventions.Material and methods. Patients with STEMI and refractory no-reflow will be randomized into 4 groups: standard therapy, intracoronary adrenaline, intracoronary verapamil, intracoronary epinephrine + verapamil. All patients will be assessed for epicardial blood flow using the Thrombolysis in Myocardial Infarction (TIMI) and Myocardial Blush Grade (MBG) scales, peak troponin levels, ST segment changes, echocardiography, magnetic roesnance imaging, and dynamic single photon emission computed tomography.Results. Based on the pharmacodynamic effects of epinephrine and verapamil, their combination is expected to have a more potent vasodilating effect.Conclusion. If the Intracoronary administration of EPInephrine and VERapamil in the refractory no-reflow phenomenon (EPIVER) study will be successful, a novel, more effective method for managing refractory no-reflow phenomenon will appear. This will ensure better preservation of left ventricular systolic function, as well as improve the prognosis and clinical course of the disease.